KRAS mutation in pancreatic cancer - Luo, Ji (Seminars in oncology, 2021)
Pancreatic cancer is a recalcitrant cancer with one of the lowest 5-year survival rates. A hallmark of pancreatic cancer is the prevalence of oncogenic mutation in the KRAS gene. The KRAS oncogene plays a critical role in the initiation and maintenance of pancreatic tumors and its signaling network represents a major target for therapeutic intervention. A number of inhibitors have been developed against kinase effectors in various Ras signaling pathways. Their clinical activity, however, has been disappointing thus far. More recently, covalent inhibitors targeting the KRAS oncoprotein have been developed. These inhibitors showed promising activity in KRAS mutant pancreatic cancer in early clinical trials. This review will present an updated summary of our understanding of mutant KRAS function in pancreatic cancer and discuss therapeutic strategies that target oncogenic KRAS signaling in this disease.